The Impact Of Foreign Direct Investment In Reducing Poverty Within The Framework Of Financing Reconstruction Syria - شيحا, مضر (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aimed at analyzing the impact of foreign direct investment on human poverty rates in Syria during the pre-war period (2000_2010), by relying on the analytical descriptive approach, in addition to the ordinary least squares method for finding the regression equation between the two variables of the study. This study concluded that there is a relatively weak impact of foreign direct investments in reducing poverty rates in Syria, and this is due to the structure of these investments, which is dominated by investments looking for natural resources (oil and gas), which are characterized by being capital-intensive, which weakens their ability to create job opportunities for local labor, and thus limiting its impact on raising the living standards of that local labor, in addition to the lack of participation of these investments in the health sector, and their weak contribution in the education sector. Therefore, the study recommended redirecting the structure of these foreign direct investments towards service investments in general _especially education and health services in particular _although the Syrian government provides these two services semi freely and in nominal prices, due to the destruction caused by the war to the facilities of these two services.